科技对三峡移民经济可持续发展的作用与对策探讨 = The impact of science and technology on the sustainable development of three gorges migration economy - 唐建华 Tang, Jianhua (2008)
This dissertation focuses the Three Gorges’ migration issues on the establishment of a new migration society from a systematic approach of migration, settlement, development and sustainable growth. More specifically, the impact of science and technology on the establishment of the new migration society will be analyzed.